Penguatan Ekonomi Desa melalui Edukasi Sertifikat Halal dan Optimalisasi Produk Kreatif Berbasis Pisang di Desa Kalikatir Kabupaten Mojokerto Jawa Timur - Rachmad Sholeh; Ghozali Ghozali; Ahfi Nova Ashriana; Khasbulloh Huda; Yusuf Rahman Al Hakim; Ina Dwi Wijayanti (Jurnal Pelayanan Masyarakat, 2026)
Village economic development based on local potential is an important strategy in improving community welfare and strengthening the sustainability of micro-enterprises. Kalikatir Village, Gondang District, Mojokerto Regency, has considerable potential in processed banana products developed by local MSMEs. However, business actors still face challenges related to halal certification understanding, product innovation, packaging, and marketing optimization. This community service activity aims to strengthen the village economy through halal certification education and optimization of banana-based creative products using a participatory approach. The method used was descriptive qualitative with observation, interviews, Focus Group Discussion (FGD), and direct mentoring techniques. The results showed that halal education increased the understanding and awareness of MSME actors regarding the importance of halal certification as an effort to improve product competitiveness. In addition, product innovation and packaging optimization succeeded in increasing the attractiveness and market value of processed banana products. Collaboration between students, village government, and community members also strengthened social participation and sustainability of local economic empowerment programs. This activity confirms that local potential-based empowerment integrated with halal literacy can become an effective strategy for strengthening village economic independence.